Dental professional's understanding of COVID-19 management: Can they contribute to medical care? - Akanksha Juneja; Amina Sultan (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The sudden appearance of the highly infectious novel coronavirus in December 2019 has created global havoc in a short time. In the present scenario where the cases are rising explosively and medical health care professionals are losing their lives to coronavirus disease 2019 (COVID-19), the role of dental surgeons needs to be redefined. OBJECTIVE: Keeping all these things into consideration; this questionnaire-based cross sectional survey was planned to understand how dental surgeons managed COVID-19 once they got infected, and how confident they are if in future they need to treat cases of COVID-19. MATERIALS AND METHODS: A cross-sectional survey was done to assess the knowledge of practising dental surgeons infected with COVID-19 of the disease and its management. RESULTS: One hundred and one respondents completed the questionnaire. Of those 81% were vaccinated while 19% were not vaccinated. Of these 50.5% felt confident that they had adequate knowledge regarding COVID-19 and can treat mild-to-moderate infections. 84.2% believed that short-term courses and workshops should be designed for dental surgeons to improve their knowledge, keeping in mind their future role in pandemic. CONCLUSION: Short-term courses need to be designed to improve the current knowledge of dental surgeons regarding COVID-19 and prepare them for future.